Effect of different rice transplanting patterns on microbial community in water, sediment, and Procambarus clarkii intestine in rice-crayfish system - Huang, Jin; Li, Jinghao; Zhou, Wenzong; Cheng, Yongxu; Li, Jiayao (Frontiers in Microbiology, 2023)
Although the microbial ecology of integrated rice-crayfish farming systems is receiving increasing attention with the expanding application area in China, the effects of rice transplanting patterns on the microbial community of water, sediment and Procambarus clarkii intestine in rice-crayfish system has yet to be determined.This study explored the microbial community present in water, sediment and intestine samples from three transplant patterns (rice crayfish with wide-narrow row transplanting, rice-crayfish with normal transplanting and pond-crayfish, abbreviated as RC-W, RC and PC, respectively) using high-throughput sequencing. The results showed that the dominant microbial taxa from sediment, surrounding water, and intestine at phylum level were Proteobacteria, Chloroflexi, Cyanobacteria, Actinobacteria, Bacteroidetes. The patterns of rice transplanting had significant effects on microbial biodiversity and species composition in surrounding water. The OTUs community richness of water under RC group was significantly higher than that of PC group and RC-W group. The OTU relative abundance of top 10 operational taxonomic units had significantly different (P < 0.05) in the water samples from the three groups. The intestinal OTU community richness of Procambarus clarkii in the three groups was positively correlated with the community richness of water. The proximity between intestinal and water samples in PCA diagram indicated that their species composition was more similar. The results also showed that rice transplanting patterns can affect intestinal microbial biodiversity of Procambarus clarkii and the intestinal microbial biodiversity correlated with water bodies. Although the intestinal microbial diversity of crayfish in RC-W group was lower than that in RC group, the relative abundance of potential pathogenic bacteria, such as Vibrio, Aeromonas, in intestine of the crayfish in the RC-W group was significantly decreased under rice wide-narrow row transplanting model. Redundancy analysis revealed that environmental parameters, such as pH, DO, nitrate, which regulate the composition of microbial community structures. This study provides an understanding for microbial response to different rice transplanting pattern in rice-crayfish farming system.